Fuzzy dynamic hybrid MCDM method for supplier evaluation and selection / Adeleh Asemi Zavareh - Zavareh, Adeleh Asemi (2014)

(untitled)
In Supply Chain Management (SCM), it is important to have good purchasing strategies to ensure optimal cost and quality of product. Supplier management is part of decision making (DM) in the purchasing process. Supplier management involves the evaluation and selection of suppliers. An accurate evaluation of suppliers can reduce the costs and improve the quality. Supplier management is complex due to multiple criteria, dynamic environment and uncertainty. Various studies have applied Multi Criteria Decision Making (MCDM) models to solve supplier management problem. However, current supplier management methods have limitations in specific situations. They do not consider the environment changes that can affect the process of evaluation and ranking. Various intelligent MCDM methods are analyzed to find suitable methods to address supplier selection problems. The DM environment with four elements (Re-ranking, homogeny, Inconsistency, population) is defined. A Fuzzy Dynamic Hybrid MCDM (FDHM) method is proposed and developed for the evaluation, ranking and selection of suppliers. The method employs Fuzzy Analytic Hierarchy Process (FAHP) for weighting of criteria. A Fuzzy Inference System (FIS) is developed to determine the impact of FAHP method and Fuzzy Technique Of Preferences Similarity to Ideal Solution (FTOPSIS). The method for evaluation of suppliers is based on impact factors. Experiments for supplier management in Mobarakeh steel company are carried out for different DM environments. FDHM method is evaluated by the satisfactorily and efficiency factors. The ability of methods to produce a ranking in high correlation coefficient with experts’ judgment, implies that the experts are satisfied with the performance of FDHM. In each experiment, the efficiency of FDHM with other fuzzy hybrid SES decision making methods in terms of accuracy and complexity is compared. The accuracy is the first priority to determine the efficiency of FDHM in supplier management. The iii complexity is calculated by the number of comparisons. In each experiment we calculate the complexity of methods in same conditions. The result shows that FDHM satisfies the expectation of the experts.